Rural Electrification Concessions in Africa : What Does Experience Tell Us? - Hosier, Richard; Bazilian, Morgan; Lemondzhava, Tatia; Malik, Kabir; Motohashi, Mitsunori; Vilar de Ferrenbach, David (World Bank, Washington, DC, 2017)
This report evaluates the use of rural electrification concessions in Africa. It provides acomprehensive overview of successful and failed cases and identifies the likely factors behindsuccesses. The research was conducted in three stages. First, a detailed desk review of rural electric concessions in Africa was undertaken to understand the landscape of concessions. Next, six in-depth, field-based country case studies were prepared. Finally, a limited desk review of the experiences with concessions and concession-like structures in both Asia and Latin America was carried out in order to provide a point of comparison for the African experience.